The liberating Gospel in China the Christian faith among China's minority peoples - Covell, Ralph R. (Grand Rapids, MI Baker, 1995)
Includes biblographical references and index.
Keywords: Minorities -- China -- missions; Missions -- China; Missions -- Taiwan